Concepts of infectious, contagious, and epidemic disease in Anglo-Saxon England - Künzel, Stefanie (2018)
This thesis examines concepts of disease existing in the Anglo-Saxon period. The focus is in particular on the conceptual intricacies pertaining to pestilence or, in modern terms, epidemic disease. The aim is to (1) establish the different aspects of the cognitive conceptualisation and their representation in the language and (2) to illustrate how they are placed in relation to other concepts within a broader understanding of the world. The scope of this study encompasses the entire corpus of Old English literature, select Latin material produced in Anglo-Saxon England, as well as prominent sources including works by Isidore of Seville, Gregory of Tours, and Pope Gregory the Great. An introductory survey of past scholarship identifies main tenets of research and addresses shortcomings in our understanding of historic depictions of epidemic disease, that is, a lack of appreciation for the dynamics of the human mind. The main body of research will discuss the topic on a lexico-semantic, contextual and wider cultural level. An electronic evaluation of the Dictionary of Old English Corpus establishes the most salient semantic fields surrounding instances of cwealm and wol (‘pestilence’), such as harmful entities, battle and warfare, sin, punishment, and atmospheric phenomena. Occurrences of pestilential disease are distributed across a variety of text types including (medical) charms, hagiographic and historiographic literature, homilies, and scientific, encyclopaedic treatises. The different contexts highlight several distinguishable aspects of disease, (‘reason’, ‘cause’, ‘symptoms’, ‘purpose’, and ‘treatment’) and strategically put them in relation with other concepts. Connections within this conceptual network can be based on co-occurrence, causality, and analogy and are set within a wider cultural frame informed largely though not exclusively by Christian doctrine. The thesis concludes that Anglo-Saxon ideas of disease must be viewed as part of a complex web of knowledge and beliefs in order to understand how they can be framed by various discourses with more or less diverging objectives. The overall picture emerging from this study, while certainly not being free from contradiction, is not one of superstition and ignorance but is grounded in observation and integrated into many-layered systems of cultural knowledge.